IMPLEMENTASI SISTEM AKUNTANSI BERBASIS AKRUAL DI DESA DAMPAKNYA TERHADAP TRANSPARANSI KEUANGAN - Afrizal Batubara; Rina Malahayati; Gundahara Gundahara (CV. Armas Suan Sejahtera, 2025)
This study aims to analyze the effect of the Implementation of Accrual-Based Accounting System (SA-Akrual) on Financial Transparency in Kuta Mijele Village, Southeast Aceh. The research background is driven by the demands of good governance and the substantial allocation of Village Funds, which require accountable and transparent management. The research method employed a quantitative approach with data collection through questionnaires distributed to 40 respondents comprising village officials and community leaders. Data were analyzed using simple linear regression with the help of SPSS 25. The results prove that the Implementation of SA-Akrual has a positive and significant effect on Financial Transparency, as indicated by a regression coefficient of 0.648 and a significance of 0.000. The SA-Akrual variable contributes 41.2% to explaining the variation in Financial Transparency, while the remaining 58.8% is influenced by other factors outside the model. Qualitative findings reveal that the mechanism of influence occurs through process standardization, improved information quality, and the creation of a clear audit trail. Key supporting factors include the leadership commitment of the village head and community participation. This study concludes that SA-Akrual acts as a catalyst for transparency but needs to be supported by enhanced human resource capacity and more effective information dissemination strategies. Practical recommendations are directed at the village government for ongoing training and innovation in presenting financial reports that are easily understood by the community